Xanthogranulomatous appendicitis: A case report - Gartoulla, RP (Journal of Institute of Medicine Nepal, 2016)
Xanthogranulomatous inflammation is a well described inflammatory condition which can involve any organ but is commonly seen in the gallbladder and kidney. Xanthogranulomatous inflammation involving the appendix is rarewith very few cases reported in the literature. Here we report a case of 19 years old girl with xanthogranulomatous appendicitis who underwent interval appendicectomy. Histopathology revealed the presence of predominance of foamy histiocytes admixed with lymphocytes and plasma cells.